The Influence of Leadership Style on Employee Work Motivation at PT. Pos Indonesia (PERSERO) Banda Aceh City - Hajriyanti, Rahmi; Imilda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The success of a company is largely determined by the role of motivation given by the leadership to its employees. With the motivation of employees, employees are expected to be able to work productively, thus providing benefits to the company. The purpose of this study was to determine the magnitude of the influence of leadership style on employee motivation. The employees involved as respondents in this study were 30 respondents, who were employees of PT. POS INDONESIA (Persero) Banda Aceh. Primary data was obtained using a closed questionnaire based on a Likert scale with five ranges. To process the data that has been collected, multiple linear regression analysis (Multiple Regression) is used with the formula Y = a + b1 X1 + b2 X2 + b3 X3 + e. The results showed that leadership style has a significant influence on employee motivation. This is indicated by the f-count of 6.88847 and the f-table of 2.92. Judging from the magnitude of the correlation coefficient (R) is 0.66546 and the magnitude of the multiple determinant coefficient (R2) is 0.44284. This shows that with the correlation (R), it means that the leadership style variable (Autocratic, Participatory, and Liberal) has a direct relationship with employee work motivation while the R2 value means that the influence of leadership style on employee work motivation can only be explained by 44.284% and the rest still influenced by other factors not examined in this study.